Study of the Quality of Health Services for Inpatient Patients BPJS Participants at the Padang Sidempuan City Regional General Hospital - Alprida Harahap; Owildan Wisudawan B; Ahmad Safii Hasibuan (Sean Institute, 2021)
Complaints about health services in hospitals are often heard from health insurance participants as a significant part, sometimes the health services obtained are not satisfactory, usually the targets are the attitude or actions of doctors or paramedics who are not good enough, inadequate facilities, drug supplies, and patient safety etc. The purpose of this study was to describe the quality of health services for inpatients participating in BPJS at the Padang Sidempuan City Regional General Hospital. This research was conducted at the Padang Sidempuan Regional General Hospital. The type of research used is a survey with a descriptive approach. The sample of this study were inpatients participating in BPJS with purposive sampling with a total of 50 samples. The results showed that 77.3% of BPJS inpatients who stated good doctor services with good health service quality, 79.5% of BPJS inpatients who stated good nurse services with good quality health services, 79.5% of inpatients 93.9% of BPJS stated that patient safety services were good with good quality health services, 88.2% of inpatient BPJS participants stated that administrative services were good with good quality health services. The conclusion is that inpatients are BPJS participants who state that doctor services are good, nurse services are good, patient safety services are good, administration is good with good health service quality.